Pendampingan UMKM dalam Pengelolaan Keuangan dan Pemasaran Digital Untuk Meningkatkan Daya Saing Sedap T-Rasya: Penelitian - Nisfi Tia Widyaningsih; Girindra Satrio Cahyo Pamungkas; Erizka Ajeng Rahmaniar; Rizky Wahyudha Rosiawan (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The development of information technology in the digital era has brought significant changes to the management of Micro, Small, and Medium Enterprises (MSMEs), particularly in the financial and marketing aspects. However, many MSMEs still lack the ability to utilize technology optimally, including the Sedap t-Rasya MSME in Lamongan Regency, which still faces challenges in financial record keeping and utilizing digital media for promotion. This community service activity aims to analyze the challenges faced by the Sedap t-Rasya MSME and provide assistance in implementing a simple digital-based financial record keeping system and optimizing marketing through social media and marketplaces. The method used was a qualitative approach through interviews and direct assistance to business owners. The results showed that prior to the assistance, financial records were non-existent, and product promotion was limited to social media. After the assistance, the MSME began implementing Excel-based financial records, established a shop account on Shopee, and managed Instagram as a more professional promotional tool. This activity is expected to improve the effectiveness of financial management and expand the marketing reach of the Sedap t-Rasya MSME, thereby enhancing its competitiveness and sustainability amidst the increasingly competitive culinary industry.